ANALISIS KEPEMIMPINAN, LINGKUNGAN, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN AR BAKERY BARON NGANJUK - Ulfiana, Annisa; Soedjoko, Dodi Kusuma Hadi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to investigate whether leadership, work environment, and work motivation significantly influence employee job satisfaction at AR Bakery Baron Nanjuk. The approach used in this study is a quantitative approach with a causal relationship method, which uses a sampling technique. The sample involved in this study were 40 employees, and data analysis was carried out through descriptive statistical techniques, classical assumption tests, multiple linear regression, calculation of the coefficient of determination, and hypothesis testing with the support of SPSS Version 25 software. The results of this study indicate that the variable leadership and work environment has no significant effect on job satisfaction. However, the variable of work motivation has a significant effect on job satisfaction. In addition, together, the, the variables of leadership, work environment, and work motivation significantly influenceatisfaction at AR Bakery Baron Nganjuk.